Faktor – Faktor Yang Mempengaruhi Penurunan Kualitas Tidur Pada Mahasiswa Fakultas Kedokteran Umsu Angkatan 2018 - Arjuna Trimulya; Batubara, Heppy Jelita Sari (Vitamin : Jurnal ilmu Kesehatan Umum, 2025)
Sleep is a basic need for every human being. Every human being needs adequate sleep in order to obtain a healthy and good body. Poor sleep quality is one of the causes of many medical ailments and has a strong relationship between physical, psychological and sleep health. According to several studies on sleep quality, a person's sleep quality is influenced by several factors such as physical activity, stress and emotion, surfing the internet, watching television and having other habits such as drinking alcohol, smoking and fast food. The student group is a group that has a fairly solid activity. Students can experience disturbances in the circadian cycle due to increased pressure from the academic environment so that groups of students do not have enough sleep. Some of the stressors from Medical Faculty students include busy class schedules, piled up assignments, anxiety before exams that affect the sleep quality of the Medical Faculty students. To determine the relationship between physical activity and emotional stress on decreased sleep quality in students of the Faculty of Medicine, UMSU class 2018. This study used an analytical descriptive method with a cross sectional design. The data was processed using the SPSS Chi-Square test in June 2022 at the Faculty of Medicine, University of Muhammadiyah North Sumatra. Based on the results of the analysis, the demographic characteristics of the average age of respondents were 22 (range 22-24) years and 97 (74%) of respondents were women, the frequency of poor sleep quality was the highest (79.4%), the frequency of light physical activity as much as (55%) and the frequency of moderate emotional stress (84%). Multivariate analysis showed that the factors that influence the decrease in sleep quality were emotional stress with p value = 0.001. Physical activity statistically did not affect the decrease in sleep quality with p value = 0.993. There is a significant relationship between emotional stress and decreased sleep quality in students of the Faculty of Medicine, University of Muhammadiyah North Sumatra, Class of 2018.